Ethical Outcomes and Business Ethics: Toward Improving Business Ethics Education - Floyd, Larry A.; Xu, Feng; Atkins, Ryan; Caldwell, Cam (Journal of business ethics, 2013)
Unethical conduct has reached crisis proportions in business (Walker et al., Wall Str J East Edn, 258(37):A1-A10, 2011) and on today's college campuses (Burke et al., CPA J, 77(5):58-65, 2007). Despite the evidence that suggests that more than half of business students admit to dishonest practices (McCabe et al. 2006), only about 5 % of business school deans surveyed believe that dishonesty is a problem at their schools (Brown et al., Coll Stud J A, 44(2):299-308, 2010). In addition, the AACSB which establishes standards for accredited business schools has resisted the urging of deans and business experts to require business schools to teach an ethics class, and fewer than one-third of businesses schools now teach a business ethics course at the graduate or undergraduate levels (Swanson and Fisher, Advancing Business Ethics Education, 2008). In this paper we briefly introduce the status of business ethics education and report the results of a survey of business students, deans of the top business schools, and business ethics subject matter experts about ten ethical outcomes. We then offer five specific recommendations to encourage business ethics faculty and decision makers to improve the teaching of business ethics.